2017
DOI: 10.1140/epjc/s10052-017-4897-3
|View full text |Cite
|
Sign up to set email alerts
|

Finslerian dipolar modulation of the CMB power spectra at scales $$2<l<600$$ 2 < l < 600

Abstract: A common explanation for the CMB power asymmetry is to introduce a dipolar modulation at the stage of inflation, where the primordial power spectrum is spatially varying. If the universe in the stage of inflation is Finslerian, and if the Finsler spacetime is non-reversible under parity flip, x → −x, then a three dimensional spectrum which is a function of wave vector and direction is valid. In this paper, a three dimensional primordial power spectrum with preferred direction is derived in the framework of Fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This way we take into account the entire light curve and not just parts of it around the critical phases. This method was applied by Derekas et al (2012) when they detected the random period jitter of a Cepheid (V1154 Cyg), and also by Li & Qian (2014) and Guggenberger & Steixner (2015) who search for potential light-time effect caused by a companion in the Kepler RR Lyrae sample. This work used the same implementation of the method what we used in Benkő et al (2016), namely the program of Derekas et al (2012) sligthly adjusted to RR Lyrae stars.…”
Section: The O−c Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…This way we take into account the entire light curve and not just parts of it around the critical phases. This method was applied by Derekas et al (2012) when they detected the random period jitter of a Cepheid (V1154 Cyg), and also by Li & Qian (2014) and Guggenberger & Steixner (2015) who search for potential light-time effect caused by a companion in the Kepler RR Lyrae sample. This work used the same implementation of the method what we used in Benkő et al (2016), namely the program of Derekas et al (2012) sligthly adjusted to RR Lyrae stars.…”
Section: The O−c Diagramsmentioning
confidence: 99%
“…The appearance of the Kepler year in the flux data has already been known (Bányai et al 2013) but here we demonstrated that this instrumental systematics affects the phases. Li & Qian (2014) identified the long periodicities in the O−C diagrams of FN Lyr and V894 Lyr, using the Kepler data, as potential light-time effect caused by companions. As we can see in Tab.…”
Section: Fourier Analysis Of the O−c Diagramsmentioning
confidence: 99%
“…In Finsler space-time, the gravitational field equation takes the form (Li & Chang 2014;Li et al 2015b;Li & Lin 2017)…”
Section: The Comoving Curvature Perturbation In Finsler Space-timementioning
confidence: 99%
“…As a special case of Finsler geometry, Randers space has been used to study the anisotropic inflation (Li et al 2015b;Li & Wang 2016;Li & Lin 2017) and the anisotropic accelerating expansion of the universe (Li et al 2015a). For the background space-time, the Finsler structure in this work is given by…”
Section: The Comoving Curvature Perturbation In Finsler Space-timementioning
confidence: 99%
See 1 more Smart Citation